DEVELOPMENT OF (Fe–B–C)-BASED FILLER FOR WEAR-RESISTANT COMPOSITE COATINGS - Sukhova, O. V.; Zdorovets, N. O. (Science and Transport Progress, 2014)
Purpose. Development of multi-alloyed filler for abrasive wear-resistant composites. Methodology. The methods of microstructural, X-ray and energy-dispersive X-ray analyses were used to achieve research purpose. Micro-mechanical properties of structural constituents and abrasive wear-resistance of composites were determined. Findings. The complete dissolution of chromium and vanadium in the borides of Fe2В and FeВ that are initial structural constituents of Fe–В–С peritectic alloys has been established. These elements primarily dissolve in iron monoboride. Dissolution of molybdenum and niobium is not practically observed. As a result the phases of Мо2В, Мо2(В,С) or NbВ2 can be seen in the structure. Alloying with chromium and vanadium increases compression strength and crack resistance coefficient, but that with molybdenum and niobium enhances total microhardness and hardness of the alloys. Structure formation of the interfaces between the filler and the binder of the composites based on МNМts 20-20 binder is governed by dissolution and diffusion processes when multi-alloyed (Fe–В–С) alloy is applied as filler of the composites. The phase and the structural composition of contact interaction zones canbe explained by re-crystallization of the filler surface layers after dissolution caused by contact with the molten binder. Consequently the macroheterogeneous structure of the composites is free of defects and strong adhesion between the filler and the binder is assured. Contact interaction intensity can be controlled by the choice of temperature-and-time infiltration regimes. Originality. The peculiarities in the formation of structure and properties of Fe2В- and FeВ-based solid solutions observed in the structure of the Fe–В–С peritectic alloys were investigated that allowed us to recommend composition of multicomponent alloy to be applied as filler of (Cu–Ni–Mn)-matrix macroheterogeneous composites. Practical value. Owing to multiple alloying of the filler based on Fe–В–С peritectic alloy with chromium, vanadium, molybdenum and niobium the abrasive wear resistance of composite coatings can be compared with that of tungsten-containing coatings, which ensures saving of expensive and deficient materials.